ABOUT INFLUENCE OF LATERAL HETEROGENEITIES IN THE EARTH UPPER MANTLE ON THE LOVE NUMBERS FOR DIURNAL TIDES - Lubkov, M. V. (Одеські астрономічні публікації, 2007)
On the base of the combined method, consisting of the Sasao, Okubo, Saito approach with the iteration procedure, allowing the coupling of the finite element method with the solution of the Laplace equation, it was defined the influence of the horizontal heterogeneities in the upper mantle on the diurnal Love and Shida numbers of the second order. It was determined, that maximum deviations due to such heterogeneities can reach 0.5 percent for Love numbers k and h, for Shida number - l the deviations don’t depend from the tidal wave frequency and approximately make up 0.2 percent. For evaluation of the accuracy of the suggested method it was carried out the comparison of the Love numbers k for the main diurnal tides, obtained on the base of the PREM - earth model, with respective results of Mathews, Buffet, Shapiro (1995) and Dehant (1987).